Peers supporting reintegration after occupational stress injuries: A qualitative analysis of a workplace reintegration facilitator training program developed by municipal police for public safety personnel. (March 2022) - Jones, Chelsea; Bright, Katherine; Smith-MacDonald, Lorraine; Pike, Ashley D; Bremault-Phillips, Suzette
Public safety personnel (PSP) are at increased risk of developing operational stress injuries. Peer-led reintegration programs (RPs) for PSP, evidence-based research is lacking. This study explored the experiences of PSP participating in a Reintegration Program Facilitator Training (RPFT) program. Participant ( n = 57) responses were collected from surveys, satisfaction and knowledge questionnaires, and a World Cafe. Four themes emerged: (1) traits of an ideal RF; (2) holistic/complementary workplace reintegration approach; (3) necessary features of the reintegration program; and (4) culture-specific considerations. While RPs hold promise, it is essential that evidence-based research be used to guide RPFT and RP spread and sustainability.